Pakistan's Public Health Surveillance System : A Call to Action - World Bank (Washington, DC, 2014)
This assessment considered three major areas of public health surveillance: (1) communicable diseases, (2) vital registration with a focus on maternal and infant mortality, and (3) non-communicable diseases and risk factors. The key recommendations for each of these areas are summarized below. A stepwise approach to implementing these recommendations should be considered in the National Action Plan. Chapter 4 summarizes some of the major cross-cutting issues and provides a minimum package to develop the public health surveillance system.